Impact of Board Characteristics, Firm Level Factors and Political Connections on Cost of Capital: Evidence from Pakistan - Muhammad Bilal Ijaz; Awais Javeed; Sahar Afshan (iRASD Journal of Management)
The purpose of the study is to analyze the impact of board characteristics, firm level factors and political connections on cost of capital. The sample of study comprises of 175 non-financial companies listed on Pakistan Stock Exchange from 2008 to 2021. Fixed effect model is used for analysis of data. The findings revealed that Increasing board independence and leverage has a negative influence on the cost of capital. Whereas, Board size, Audit committee size impact the cost of capital positively. The study resolute that the cost of capital is not influenced by political connections, firm size, or institutional ownership. The research identified that there was a decline in the cost of capital, along with an increase in board independence and leverage. In addition, the cost of capital is unaffected by political connections, the size of firms and institutional shareholdings. In contrast, the cost of capital grew due to an increase in the size of the Board and the Audit Committee. The study suggests that In Pakistan non-financial firm’s maximum family own business and very low focus on management and foreign owners. Alternative prospective of managerial and foreign ownership firms should minimized the agency problems as family ownership. And for the best improvement of corporate governance board of directors should bring a transparency, accountability and fairness financial reporting.